Proximal Sciatic Nerve Intraneural Ganglion Cyst. (1st December 2009) - Swartz, Karin R.; Wilson, Dianne; Boland, Michael; Fee, Dominic B.
Abstract : Intraneural ganglion cysts are nonneoplastic, mucinous cysts within the epineurium of peripheral nerves which usually involve the peroneal nerve at the knee. A 37-year-old female presented with progressive left buttock and posterior thigh pain. Magnetic resonance imaging revealed a sciatic nerve mass at the sacral notch which was subsequently revealed to be an intraneural ganglion cyst. An intraneural ganglion cyst confined to the proximal sciatic nerve has only been reported once prior to 2009.